mHealth Series: Measuring maternal newborn and child health coverage by text messaging - a county-level model for China - Yanfeng Zhang; Li Chen; Michelle H. M. M. T. van Velthoven; Wei Wang; Li Liu; Xiaozhen Du; Qiong Wu; Ye Li; Josip Car (Edinburgh University Global Health Society, 2013)
Effective interventions in maternal, newborn and child health (MNCH), if achieving high level of population coverage, could prevent most of deaths in children under five years of age. High-quality measurements of MNCH coverage are essential for tracking progress and making evidence-based decisions.